Sponsorship in sports marketing: The effects of sports sponsorship on football fans' sponsor awareness, exposure, attitude, perceived congruence, purchase intentions and simultaneous sponsorship with a rival club - Oliveira, Diogo Matos dos Santos de Magalhães (2020)
Purpose: As football is a connection/loyalty-based sport, this study aimed to investigate the effects that a simultaneous sponsorship of two rival clubs has on the sponsor itself, as well as understand the reaction that team supporters display toward that situation. Another aim was to examine the existence of congruency of attributes between the sponsor brand and either of the clubs, in addition to understanding the effects of exposure on attitudes towards the sponsor and on purchase intentions, towards sponsor. Methodology: First a literature review was conducted on the topics of sports sponsorship, brands, congruency, attitude towards sponsor and purchase intentions. Next, hypotheses were formulated and tested through an online survey applied midst sports enthusiasts. Lastly, the data was analysed and the hypotheses were verified. Findings: This study uncovered that different types of exposure and level of involvement translate into different levels of awareness; awareness takes a positive effect on attitude towards sponsor and, the latter on purchase intentions. Additionally, it was demonstrated that a brand sponsoring two rival clubs does not affect both sets of fans in the same regard (when having into account the set of attitudes and the awareness) (based on the articulation of values and traits), hence, exhibiting the importance of congruent communication. Contributions: This study adds to previous research by encompassing the study of the effects of a simultaneous sponsorship of two rival clubs in a different cultural setting. Furthermore, this study considered the different level of exposition of a sponsor and its effects.